Association between the metabolically healthy obese phenotype and the risk of myocardial infarction: results from the Kailuan study. Issue 6 (December 2018) - Xu, Yijie; Li, Haibin; Wang, Anxin; Su, Zhaoping; Yang, Guang; Luo, Yanxia; Tao, Lixin; Chen, Shuohua; Wu, Shouling; Wang, Youxin; Guo, Xiuhua
Abstract : Objective: This study aimed to determine if the metabolically healthy obese (MHO) is associated with an increased risk of myocardial infarction (MI) in Chinese population. Design: The Kailuan study is a community-based prospective cohort study. Methods: BMI and metabolic syndrome (MetS) were assessed in 91 866 participants without a history of MI or stroke. Participants were categorised into six mutually exclusive groups according to the BMI-MetS status: normal weight (BMI:  ≤ 18.5to < 24.0 kg/m 2 ) without MetS (MH-NW), normal weight with MetS (MUH-NW), overweight (BMI:  ≤ 24.0to < 28.0 kg/m 2 ) without MetS (MH-OW), overweight with MetS (MUH-OW), obese (BMI ≥ 28.0 kg/m 2 ) without MetS (MHO) and obese with MetS (MUO). The hazard ratio (HR) with 95% CI was calculated for the incidence of MI using a multivariable Cox model. Results: A total of 6745 (7.34%) individuals were classified as MHO. During a median 8-year follow-up, 1167 (1.27%) participants developed MI. The MHO group had an increased risk of MI (HR: 1.76, 95% CI: 1.37–2.25) in comparison with the MH-NW group after adjusting for potential confounding variables. After a similar adjustment, the risk of MI was significantly elevated in the MUH-NW (HR: 1.62, 95% CI: 1.28–2.05), MUH-OW (HR: 1.98, 95% CI: 1.67–2.35) and MUO group (HR: 2.06, 95% CI: 1.70–2.49). Conclusions: MHO subjects showed a substantially higher risk of MI in comparison with MH-NW subjects. That said, even without measurable metabolic abnormalities, obesity was associated with a higher risk of MI.